ASSESSMENT AND ANALYSIS OF REGIONAL FEATURES OF RESOURCE- SAVING LAND USE FOR SUSTAINABLE MANAGEMENT - Anatolii KUCHER; Alina HRECHKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this study is a comprehensive assessment and mapping of resource-saving land use in terms of regions of Ukraine as a basis for the organization of sustainable land management in the agricultural sector. The rating of regions of Ukraine was compiled by a comprehensive assessment of land use savings, which made it possible to identify regional features and reserves of increasing resource saving land use. It was found that land capacity index had the most significant impact on the degree of land use savings. This paper is one of the first article where a comprehensive assessment and analysis of the current state of resource-saving of land use in the agriculture of the regions of Ukraine and the search for factors of increasing land use savings based on regional differences was carried out, making a contribution to the lack of literature on this issue. The results of the study can be used to make economically sound management decisions to increase land use savings in Ukrainian regions. The practical use of the obtained results can help to improve the efficiency and effectiveness of sustainable land management at national and regional levels.